PSYCHO-TRAINING PROGRAM FOR FORMATION OF PSYCHOLOGICAL READINESS FOR RISK OF MILITARY PERSONNEL OF THE NATIONAL GUARD OF UKRAINE - Lyman, A. (Honor and Law, 2020)
The article is devoted to the issue of developing a psycho-training program “Formation of psychological readiness for risk of military personnel of the National Guard of Ukraine”. The definition of the concept of “training” is given; the general stages of conducting training programs are given. The author provides an interpretation of the term “psychological readiness for risk of military personnel of the National Guard of Ukraine”, its structural components. Psychological readiness for the risk of the military personnel of the National Guard of Ukraine can be defined as the ability of a person to attract all his potential (personal characteristics, knowledge, skills and abilities) and internal and external resources in order to achieve the planned plan of action in previously unknown circumstances. The psychological readiness for risk of military personnel of the National Guard of Ukraine has three main components: focus on the task, high level of interaction, ability to control your fear. The psycho-training program is designed to optimize the development process of the components of psychological readiness for risk of military personnel of the National Guard of Ukraine. This solves a number of problems: the formation of volitional self-regulation (decisiveness, courage, will); the formation of a communicative skill (trust, tolerance, sociability); the development of the ability to have a positive attitude towards oneself and adequate self-esteem, evaluating other people and their relationships; formation of the ability to reflection; the formation and development of the ability to predict people’s behavior and predict the results of their own activities; development of personality traits inherent in a professional military personnel; enriching professional and life experience. The author’s questionnaire for evaluating the effectiveness of the psycho-training program “Formation of psychological readiness to risk for military personnel of the National Guard of Ukraine” is presented.